The nurse in sexual abuse child suspicion attention: a phenomenology approach - Lia Leão Ciuffo; Benedita Maria Rêgo Deusdará Rodrigues; Janice Machado da Cunha (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2009)
Abstract: Introduction: This study brings reflexions and contributions about nurse attendance in child sexual abuse suspicion, in view the gravity and seriousness of this issue in society and the possibilities of actions to be undertaken by nurse face the child and his family, considering health promotion, protection and prevention. Objective was to analyze nurse actions in child sexual abuse suspicion context Methodology: qualitative research based on sociological phenomenology of Alfred Schutz, which emphasizes social relations and define the action as human conduct with a purpose, namely, has an intent, the In - Order- To motives of the action, that were captured by phenomenological interview. The questions that guided the interview were: When you attend a child with sexual abuse suspicion, what do you do? ; What you have in mind with nurse actions triggered in this type of attendance? Why? Results: The analysis of speech allowed the apprehension of four categories: interact with other professionals for child care; establish a dialogue and an open allowing, a care with a prospect from the other, to attend the children and fulfilling the routines of the unit.  Conclusions: From interviews comprehension and interpretation the understanding was that nurse's actions can propel nurses in child health area research and offering possible interferences in family and child assistance and in yours healthy growing and development. Relevance to clinical practice: the study contributes to a better  attendance and identification of child sexual abuse suspicion by the nurse and a wide vision in violence cases assistance.   Keywords: Nursing. Child. Sexual abuse. Phenomenology.